Mel Brooks' The producers [videorecording (DVD)] - Brooks, Mel, 1926-; Morris, John, 1926-2018; Blagman, Norman; Hartig, Herb (MGM DVD., 2003)
A legendary producer and his mild-mannered accountant face catastrophe when their play unexpectedly becomes a success.